Informative significance of indicators of physical preparedness and morphofunctional state in the structure of the motor system of 9–10 years old pupils - Красова, Ірина; Красов, Олександр (Slobozhanskyi Herald of Science and Sport, 2019)
Irina Krasova & Oleksandr Krasov The article presents the results of the factor analysis of the indicators of physical preparedness, functional status and physical development of pupils of primary school age. Identified leading factors affecting the state of the motor system of children 9–10 years old, which allows to determine the direction of pedagogical influences that will improve the efficiency of the process of physical education in primary school. Purpose: to determine the presence and informative significance of the interrelations of indicators of physical preparedness, functional status and physical development of primary school pupils. Material & Methods: the study was conducted in the secondary school No. 2 in Pereyaslav-Khmelnitsky, 115 pupils of 3–4 classes at the age of 9–10 years took part in the study. The following methods were used: theoretical analysis and synthesis of scientific and methodological literature data; pedagogical methods (observation, experiment, testing); anthropometry; physiological research methods (pulsometry, spirometry, Shtange and Gencha tests, Rufie test) methods of mathematical statistics (correlation and factor analysis). Results: the informative significance of the main components in the general structure of the motor system of boys and girls 9–10 years old has been established. Conclusion: revealed significant relationships between the components of physical preparedness, functional state and physical development, which have certain gender and age differences, but despite these differences in the factor structure of the motor activity of children 9 and 10 years old, it can be noted that there are general tendencies, which consist in the dynamic, heterochrony of development and the relationship of its main content components.